Effects Of Board Characteristics On Financial Sustainability Of Quoted Nigerian Banks - Maimako, Livinus Nkuri; Latiff, Ahmed Razman Abdul; Yusoff, Wan Fadzila Wan (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2024)
Using Agency theory to examine the relationship between board characteristics and corporate governance financial sustainability. Board size, diversity, and independence are autonomous, but financial leverage is controlled. This study examined how board features impact Nigerian banks' financial sustainability. Stata statistical tool was used to assess how board independence, diversity, and size impact financial sustainability in a convenience sample of thirteen Nigerian banks operating on the Nigerian stock exchange from 2014 to 2020. Financial leverage-controlled board characteristics. Independent board members statistically increased long-term financial sustainability. A company's long-term financial viability may improve with a board with fewer outside demands and conflicts. Financial sustainability requires independent boards of directors. Board size did not affect financial sustainability or gender diversity. Despite their potential benefits, such as broader viewpoints and improved decision-making, board diversity and size did not significantly influence the financial sustainability of the stated Nigerian banks. Diverse boards improve decision-making and widen viewpoints. Financial leverage as a control variable influences corporate viability. Due to financial risks and volatility, high financial leverage may hurt banks' long-term existence. These studies explain how corporate governance affects a company's long-term financial survival. An independent board of directors is necessary for a bank's long-term financial sustainability. The study concluded that board size and diversity may not guarantee long-term financial sustainability. Duality, organisational scale, and their interaction must be studied to understand board traits and financial sustainability